Effect of nutrition behavior change communication on nutrition knowledge and dietary practices of pregnant adolescents in West Arsi, Central Ethiopia: a cluster randomized controlled trial - Adane Tesfaye; Adane Tesfaye; Kefyalew Taye Belete; Dessalegn Tamiru; Tefera Belachew (Frontiers in Nutrition)
ObjectiveThis study investigated the effect of communication about nutritional behavior changes on the nutritional knowledge and dietary practices of pregnant adolescents in the West Arsi Zone, Central Ethiopia.MethodsA two-arm parallel cluster randomized controlled trial was conducted in West Arsi, Central Ethiopia, to assess a Nutritional Behavioral Change Communication (NBCC) intervention based on the Health Belief Model (HBM). Implemented by the Alliance for Development (AFD) from 16 weeks of gestation, the intervention included food preparation demonstrations and NBCC sessions for pregnant adolescents and their husbands. The study involved 207 and 219 pregnant adolescents in 14 interventions and 14 control clusters, respectively. The primary outcome was dietary practice, and the secondary outcome was nutritional knowledge. Conducted from October 15, 2022, to July 15, 2023, the intervention group attended four counseling sessions, while the control group received standard nutritional counseling. Generalized estimating equations and the difference-in-differences method were used to estimate the net treatment effect.ResultsThe mean age of the study participants was 17.8 ± 1.2 years, ranging from 15 to 19 years. The appropriate dietary practice rate increased by 20.3 percentage points in the intervention group and decreased by 5.6 percentage points in the control group. After controlling for possible confounders, the odds of appropriate dietary practices increased by 13% in the comparison group [AOR = 1.13; 95% CI = 1.02, 1.2], and pregnant adolescents in the intervention group had an AOR which was 3.7 times that of the comparison group in appropriate dietary practices [AOR =4.2, 95% CI = 2.6, 5.3]. The odds of good nutritional knowledge increased in both groups, however, the NBCC group had an increase 5.5 times (95%CI: 3.8, 8.1) that of the comparison group.ConclusionNBCC through AFDs based on the HBM is an effective approach for increasing the proportion of pregnant adolescents who practice appropriately and have good nutritional knowledge.Clinical trial registrationPACTR202203696996305, Pan African Clinical Trials Registry.